Model Kepemimpinan dan Pengembangan Kreativitas dalam Pengelolaan Destinasi Wisata Budaya Saung Angklung Udjo - Budiman Mahmud Musthofa (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
The rapid cultural development affected by globalization has had many impacts on local cultures in Indonesia. The dynamics of development and setback of cultural management are interesting to study considering that in the current era of the creative economy, culture is the main capital capable of driving the community's economy, one of which is through the development of cultural tourism destinations. Management of tourist destinations and various attractions requires leadership, creativity and support from its culture. This study was conducted through a qualitative method to explore in-depth information about the leadership model and the development of creativity in the management of cultural tourism destinations through a case study of Saung Angklung Udjo. This research shows that leadership in managing cultural tourism destinations requires creative strength and support from the community and culture in order to achieve long-term success and sustainability. Evidently, for more than 54 years Saung Angklung Udjo has continued to grow and contribute to society and preserve Sundanese culture and become a national pride on the global level